“It is the best Tool we have, but that doesn’t mean it’s a Good Tool”: Czech Civically Engaged Youth Actors on Tackling the Ambiguity of Using Digital Media - Karolína Šimková; Lydie Kárníková (Media&Jornalismo)
This paper explores the ambiguities of using digital media in youth’s civic engagement, acknowledging the unprecedented transformation of the senses of public and private, and the pivotal role of the digital context in shaping citizenship. It presents results from a thematic analysis of post-sorting interviews conducted within a Q research among civically engaged youth actors aged 13-18 (n=20) from Czechia, mapping their experiences with digital media. The study identifies six key themes that point to the ever- present balancing of the risks and opportunities in pursuing the participants’ agendas online. The results reveal a high level of online resilience and digital literacy of the participants, exposing coping strategies they adopt while navigating the online spaces. The study also reports on the transformed notion of sociality, pointing to the glocal implications for active engagement in the digital age, which allows garnering support from peer groups and communities on a transnational basis.